HIV-1 Resistance Dynamics in Patients With Virologic Failure to Dolutegravir Maintenance Monotherapy. (29th March 2018) - Wijting, Ingeborg E A; Lungu, Cynthia; Rijnders, Bart J A; van der Ende, Marchina E; Pham, Hanh T; Mesplede, Thibault; Pas, Suzan D; Voermans, Jolanda J C; Schuurman, Rob; van de Vijver, David A M C; Boers, Patrick H M; Gruters, Rob A; et al.
Abstract: Background: A high genetic barrier to resistance to the integrase strand transfer inhibitor (INSTI) dolutegravir has been reported in vitro and in vivo. We describe the dynamics of INSTI resistance–associated mutations (INSTI-RAMs) and mutations in the 3ʹ-polypurine tract (3ʹ-PPT) in relation to virologic failure (VF) observed in the randomized Dolutegravir as Maintenance Monotherapy for HIV-1 study (DOMONO, NCT02401828). Methods: From 10 patients with VF, plasma samples were collected before the start of cART and during VF, and were used to generate Sanger sequences of integrase, the 5ʹ terminal bases of the 3ʹ long terminal repeat (LTR), and the 3ʹ-PPT. Results: Median human immunodeficiency virus RNA load at VF was 3490 copies/mL (interquartile range 1440–4990 copies/mL). INSTI-RAMs (S230R, R263K, N155H, and E92Q+N155H) were detected in 4 patients, no INSTI-RAMs were detected in 4 patients, and sequencing of the integrase gene was unsuccessful in 2 patients. The time to VF ranged from 4 weeks to 72 weeks. In 1 patient, mutations developed in the highly conserved 3ʹ-PPT. No changes in the terminal bases of the 3ʹ-LTR were observed. Conclusions: The genetic barrier to resistance is too low to justify dolutegravir maintenance monotherapy because single INSTI-RAMs are sufficient to cause VF. The large variation in time to VF suggests that stochastic reactivation of a preexisting provirus containing a single INSTI-RAM is the mechanism for failure. Changes in the 3ʹ-PPT point to a new dolutegravir resistance mechanism in vivo. Clinical Trials Registration: NCT02401828. Abstract : The genetic barrier to dolutegravir maintenance monotherapy resistance is too low. Stochastic reactivation of a preexisting provirus containing a single integrase strand-transfer inhibitor resistance–associated mutation could explain virologic failure. 3ʹ-polypurine tract changes suggest a new dolutegravir resistance mechanism in vivo.